OSCE Outcome and Nursing Students' Perceptions and Clinical Performance - Hassan, Eman M Gaber; Lewis, Sharell; kannan, Latha S; Sivapalan, Nisha; Jiji, Darling B. (International Journal of Membrane Science and Technology, 2023)
The objective of the research was to correlate between clinical performance of the nursing students and their perception towards OSCE and their OSCE exam results. A Comparative cross-sectional study was conducted among 224 Female students (167 female students and 57 male students) who enrolled in the clinical courses from level 4 to 8 in the department of nursing; sample were selected through stratified random sample method. A questionnaire was used to assess the students’ perception towards OSCE; whereas to assess the correlation between nursing students’ perceptions and their OSCE exam results and to find the correlation between nursing students’ clinical performance score, lab score and their OSCE exam results, the real grades were taken from each course. Current study showed that students had a positive overall impression of the OSCE exam (M = 41.3, SD 12.7). Students' attitudes towards the OSCE exam were rated on a mean scale of 11 (SD 3.45). Researchers found positive correlation between the students' OSCE grade and their lab competency grade (r s = .445, P = <0.001) and their clinical performance grade (r s = .503, P = <0.001) grades. However, there was no relationship (r s =.085, P =.207) between the students’ OSCE grade and their perception toward the OSCE exam. The majority of respondents were identified to have positive attitudes towards OSCE as well as overall positive impression of the OSCE exam. OSCE is a reliable and valid assessment tool in the nursing profession. OSCE at the same time can inspire students' critical thinking and promote their communication skills. Through the continuous application of OSCE in nursing education from the beginning, it may have some potential impact on the clinical field.